COVERAGE OF VIOLENCE AGAINST CHILDREN IN SERBIAN DAILY NEWSPAPERS - Kovacevic, Milica D. (Politeia, 2021)
Violence against children arouses significant public interest as a phenomenon that opposes the most appreciated social interests. Media coverage of this topic has been conditioned by the need of the public for complete and truthful reporting, and, at the same time, by the need of media to survive in the increasingly saturated media market. The question is whether the race for the most current and intriguing media content endangers fulfillment of obligations related to the protection of interests of minors and obligations stipulated by the law. The aim of this paper is to point to the aspects of reporting on violence against children that could be improved in the future. Therefore, after the introductory considerations about violence against children and media reporting on this topic and after the review of scientific literature in this field, the central part of the paper is devoted to the analysis of media coverage of three Serbian daily papers on violence against children. The author concludes that positive regulations and professional codes are respected, but that reporting does not always serve an educational and preventive purpose, and that the protection of the dignity of victims is not at a satisfactory level at all times.